PELATIHAN DAN PENDAMPINGAN TUTOR LBB DALAM PENGEMBANGAN MEDIA EDUTAINMENT SEBAGAI UPAYA PENINGKATAN LITERASI ANAK - Ahmad Zaenuri; Saeful Anam (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service activity aims to empower teachers at the Taman Pintar Lamongan Tutoring Institute in developing interesting and interactive edutainment media for the material of introducing the names of the prophets. This effort is carried out as a strategy to improve children's literacy, especially in religious education. The methods used include training, mentoring, and evaluation in creating edutainment-based media such as animated videos, educational games, and interactive books. The results of this activity show that teachers have increased understanding and skills in designing innovative learning media. The media produced is able to increase children's interest and participation in the learning process. The sustainability of this program is expected to strengthen the role of teachers in creating a fun learning environment and supporting the development of children's literacy holistically. Thus, this program contributes to improving the quality of learning in religious-based tutoring institutions.